PRAKTIK PEMBAGIAN WARIS ADAT DUSUN RECOBANTENG DESA SUWARU KECAMATAN PAGELARAN KABUPATEN MALANG PERSPEKTIF HUKUM ISLAM - Ulum, Bahrul (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2022)
Islam as the last sawawi religion to come down to this world is certainly equipped with a comprehensive set of rules and teachings. He has perfected the previous Heavenly Religions elegantly and massively. This religion also does not escape introducing a set of rules regarding inheritance, which in general assigns a larger share of inheritance to the male line than the female line.In Recobanteng Hamlet, Suwaru Village, Pagelaran District, Malang Regency, there has been a practice of dividing inheritance from generation to generation by way of customary inheritance practices, where the son's share is equal to the daughter's share. Of course this is interesting to study in depth academically from a sharia perspective.The following article seeks to find this perspective by using a socio-anthropological approach combined with a sharia law perspective. From field observations, it was found that the people of Recobanteng Hamlet, Suwaru Village, Pagelaran District, Malang Regency share inheritance equally between men and women with consideration of humanity and justice. According to Syar'i, this kind of practice can still be justified by looking at the tasoluh principle, by distributing it first before the father or mother dies, even though the actual acceptance is only carried out after the two people have died.